Changes in countermovement vertical jump force-time metrics across different competitive levels in women`s volleyball - Cabarkapa, D.; Cabarkapa, D.; Bankovic, V.; Long, H.; Philipp, N.; Fry, A. (International Journal of Strength and Conditioning, 2025)
As one of the most fundamental skills in volleyball, the countermovement vertical jump (CVJ) has been commonly implemented as a non-invasive and time-efficient method for the assessment of lower-body neuromuscular function. The purpose of the present study was to examine differences in CVJ performance between three different competitive levels in female volleyball players (i.e., national team [n=20], professional league [n=16], collegiate [n=16]). While standing on a uni-axial force plate system sampling at 1000 Hz, athletes performed three maximal-effort CVJs with no arm swing (i.e., hands on the hips during the entire movement). Each jump was separated by a 10-15 second rest interval to minimize the possible influence of fatigue. Significantly greater eccentric braking impulse, peak velocity, peak force, mean and peak power, vertical jump height, reactive strength index-modified, countermovement depth, and shorter braking phase, eccentric duration, and contraction times were observed for the national team and professional players when compared to collegiate athletes. Also, national team players demonstrated significantly greater eccentric braking impulse, peak velocity, mean and peak power, reactive strength index-modified, and countermovement depth than professional volleyball players. However, during the concentric phase of the CVJ, the only significant differences observed were between national team players and collegiate athletes, where national team players exhibited significantly greater peak velocity, impulse, and mean and peak power. Thus, it can be concluded that higher-level players may be more capable of effectively utilizing the eccentric phase of the CVJ and executing the stretch-shortening action more rapidly, which contributes to better CVJ height.